PENGARUH PELATIHAN, KOMPETENSI DAN SISTEM INFORMASI MANAJEMEN TERHADAP KINERA STAF AKADEMIK DI POLITEKNIK LP3I JAKARTA - Lestariningsih, Widiarti (POLITEKNIK LP3I JAKARTA, 2021)
This study aims to determine the effect of training, competence and Management Information Systems on the performance of academic staff at the Polytechnic LP3I Jakarta. Where the independent variables, namely Training (X1), Competence (X2), and Management Information Systems (X3) affect the dependent variable, namely Academic Staff Performance. The research was conducted at the Polytechnic LP3I Jakarta with a total of 52 respondents. Data collection was carried out using a closed questionnaire instrument with five rating scales from strongly disagree to strongly agree. The research was conducted quantitatively by describing the research data and conducting inference analysis. Simple and multiple regression analysis was used as an analytical tool, while hypothesis testing was carried out by t-test and F-test. The study resulted in four main findings in accordance with the proposed hypothesis, namely: 1) Training does not have a significant effect on Academic Staff Performance, 2) Competence does not have a significant effect on Academic Staff Performance, 3) Management Information Systems have a positive and significant influence. on the Performance of Academic Staff, 4) Training, Competence, and Management Information Systems together have a positive and significant influence on the Performance of Academic Staff. Based on these findings, it is recommended that efforts to improve employee performance be made to improve Training, Competence, and Management Information Systems as well as further research so that training and competence have a positive and significant impact on Academic Staff Performance.Keyword : Training, Competence, Management Information System, Academic Staff Performance